Constructs of Teaching Writing in Research About Literacy Teacher Education. (June 2019) - Bomer, Randy; Land, Charlotte L.; Rubin, Jessica Cira; Van Dike, Laura M.
This review of empirical research focused on the preparation of writing teachers synthesizes findings from 82 articles published between 2000 and early 2018. The new understandings generated through this analysis are presented in two sections. First, we provide an overview of how the studies we reviewed draw from and circulate dominant discourses of writing, leading to a call for more transparency and clarity on the part of scholars who study writing and writing pedagogy. Then, we explore experiences in literacy teacher education that may shift the writing identities, beliefs, or teaching practices of prospective writing teachers. We position these shifts as being potentially disruptive to the often uninterrupted circulation of powerful discourses in important and generative ways, since the teaching of writing in the 21st century must break from inherited traditions to best prepare writers to use their voices actively and confidently in the world.